Syllabus Cours Gestion des Risques Climatiques - SOW, Sadibou (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The Climate Risk Management course, taught as part of the Master 1 in Agricultural and Rural Development at ISFAR's Alioune Diop University in Bambey, aims to equip students with the tools they need to understand and manage the effects of climate change in the agricultural sector. It is coordinated by Dr Sadibou Sow and forms part of the "Environmental Management" teaching unit. The 25-hour programme (15 hours of lectures and 10 hours of tutorials) aims to familiarise students with climate concepts, available data, forecasts and adaptation strategies in an uncertain context.